Coupling between fluids and rock deformation in the continental crust : Preface - Japas, Maria Silvia (2019)
Fluids are essential and widespread components of the Earth crust. They regulate the main process of mass and energy transport, conditioning the geochemical and geophysical evolution of thecrust (Bredehoeft and Norton, 1990) and, consequently, its properties and mechanical behavior. The coupling between fluids, rock deformation, and heat are crucial engines for plate tectonics, playing a leading role in the rheology and evolution of the lithosphere (e.g. Jamtveit et al., 2000; Kennedy and van Soest, 2007; Thompson,2010; Miller, 2013; Yardley and Bodnar, 2014; Hirauchi et al., 2016; Menzies et al., 2016; Plümper et al., 2017; Vizán et al., 2017). They strongly contribute to the viability of the Wilson cycle, since cyclic redistribution of fluids guarantees the survival of a dynamic Earth (Fyfe, 1985, 1997; Bercovici, 1998; Ribeiro, 2002; Bercovici et al.,2015, chap. 7.07; Tajima et al., 2015). The influence exerted by fluids on rock deformation (and vice versa) is significant, regardless of the tectonic setting (e.g. Oliver, 1986; McCaig et al., 2000; Doubre and Peltzer, 2007; Naganjaneyulu and Santosh, 2011; Suppe, 2014; Beaudoin et al., 2014; Williams et al., 2015; Zheng et al., 2016), crustal level (e.g. Sibson, 1994; Cosgrove, 1995; Cox, 2002; Hobbs and Ord, 2018; Papeschi et al., 2018) and scale (e.g. Carter et al., 1990; Holyoke and Kronenberg, 2013; Tajima et al., 2015).